PERCEIVED COMPETENCE AND SOCIAL ACCEPTANCE ASSESSMENT IN PORTUGUESE YOUNG STUDENTS WITH AND WITHOUT DOWN SYNDROME: A PRELIMINARY ANALYSIS - Campos, João Maria; Ferreira, Pedro José; Gaspar, Miguel Pedro; Irineu Gorla, José (European Journal of Adapted Physical Activity, 2008)
The study of self-perceptions in groups with disability is an emergent area of research in Portugal and additional evidence is needed concerning Perceived Competence and Social Acceptance of young students with Down Syndrome (DS). The main purpose of this research was to examine the reliability of a Portuguese version of the Dutch Pictorial Scale of Perceived Competence and Social Acceptance (Vermeer & Veenhof, 1997) to be used in children with and without DS. A second purpose was to assess hypothetical differences in Perceived Competence and Social Acceptance among young male and female students with and without DS. Two groups were analysed including 30 participants without DS aged 4 and 5 years old, 15 females (M = 4.40, sd = .51 yr.) and 15 males (M = 4.40, sd = .51 yr.) attending the kindergarten and 47 participants with DS aged 8 to 20 years old, 21 females (M = 14.95, sd = 2.50 yr.) and 26 males (M = 14.50, sd = 3.29 yr.) attending special schools for children with intellectual disabilities. A Portuguese version of the PSPCSA was used to assess Perceived Competence and Social Acceptance in both groups with and without disability. Results from internal consistency and test/retest reliability measures revealed that this version was appropriate to be used with children with DS from both genders. Gender differences in this study revealed that female students with DS perceived higher levels of Physical Competence but lower levels of Acceptance by their peers when compared with female students without DS. On the other hand, male students with DS felt less accepted by their peers but perceived higher levels of Parental Acceptance when compared with their male colleges without DS.
Keywords: Self-perceptions; Perceived Competence; Social Acceptance; Down Syndrome; Children